Institutional Evaluation in Basic Education Schools: a participation-oriented approach - Adilson Dalben (Universidade Estadual Paulista Júlio de Mesquita Filho, 2010)
The present work is a synthesis of my Master's Degree dissertation in which I tried toidentify the factors that have influenced the implementation of Participatory InstitutionalEvaluation in a public primary school of the periphery of Campinas, a Brazilianmunicipality in the state of Sao Paulo. Based on the concept of negotiated quality, theenactment of the institutional evaluation model proposed required the constitution ofan Evaluation Commission by representatives of diverse actors of the school community.The research consisted of a qualitative case study, using data collected from October2005 to December 2006, when I entered the school environment in order to support theschool to develop its evaluation process. Four categories of analysis were constructedto reflect on the school political pedagogical project, the educational culture of theschool principal, the nuances of participation and the potentialities of participativeinstitutional evaluation. The results acknowledge the potential of participative institutionalevaluation as a means for democratic management and for technical and politicalcapacity building at the school level aimed at overcoming problems faced by theschool.